2020
DOI: 10.22540/jfsf-05-102
|View full text |Cite
|
Sign up to set email alerts
|

Are the group-based interventions improving the functional exercise capacity and quality of life of frail subjects with chronic heart failure?

Abstract: Objectives: Frail subjects with chronic heart failure (CHF) often demonstrate limited tolerance of exertion, shortness of breath, and reduced walking capacity resulting poor quality of life (QoL). The aim of this study was to quantify the improvements in functional exercise capacity (FEC) and QoL among Bulgarian frail subjects with CHF performed group-based high-intensity aerobic interval training (HIAIT)/m-Ullevaal intervention and to compare it with moderate intensity continuous training (MICT) protocol. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Seven studies evaluated CR programs in chronic heart disease, including patients with HF (Table 3): [21][22][23][24][25][26][27][28] Studies were excluded if they were not in English, were systematic reviews or if they did not include an intervention.…”
Section: Cr Programsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seven studies evaluated CR programs in chronic heart disease, including patients with HF (Table 3): [21][22][23][24][25][26][27][28] Studies were excluded if they were not in English, were systematic reviews or if they did not include an intervention.…”
Section: Cr Programsmentioning
confidence: 99%
“…26 Reeves et al reported a significantly greater improvement in the SPPB at 6 months in ADHF patients randomized to a 12-week multidomain physical rehabilitation program compared with control patients receiving usual care. 26 In a single-center study from Bulgaria, Papathanasiou 25 randomized 120 frail patients with HF to either high-intensity aerobic interval training (HIAIT) or moderate intensity inpatients with cardiovascular disease. The proportions of the study populations with a diagnosis of HF in these studies were 23%, 53% and 100% respectively.…”
Section: Data Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second lesson from this study is that using the 6MWT as an endpoint is valuable but should be considered with its limitations. Although the 6MWT has been used in previous HF studies to measure exercise capacity 28 and can measure changes over time, ceiling effects can occur. In patients with preserved exercise capacity, the ceiling effect may be a limitation to consider the lack of improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigations found that a higher-intensity resistance component in the training resulted in a reduction in the blood pressure, and that greater muscle strength has an inverse association with the blood pressure, especially in older individuals [49][50][51][52]. Regular exercise is beneficial for older individuals to prevent CV events; age should not be a contraindication for exercise [53,54].…”
Section: Discussionmentioning
confidence: 99%